Interested in Engineering Programme, students choose UMP - Nor Salwana, Mohammad Idris (2021)
PEKAN, 1 August 2021 - Due to his deep interest in Mechanical Engineering, Aqil Danish Ady Azrul, 18, asked a lot of questions to get feedback about the programme and find information about the universities that offer the programme.